Impact of nutrient density diet with emulsifier supplementation on apparent total tract digestibility and ileal amino acid digestibility in broilers - Shanmugam Suresh Kumar; Jae Hong Park; In Ho Kim (Poultry Science)
Emulsifiers play a diverse role in the livestock industry. As a feed additive, it aids the digestion and absorption of added fat in feed to increase the productivity of broilers. The study aimed to investigate the effect of nutrient density levels and emulsifier supplementation on apparent total tract digestibility (ATTD) and apparent ileal digestibility (AID) in broilers. A total of 60 14-days- old Ross broiler chickens were randomly allocated into 4 group with 5 replicates and 3 chicks per cage for 14 days (phase 1 days 1 to 7 and phase 2 days 8 to 14). ATTD and AID were evaluated on days 7 and 14 using indigestible indicator method. Dietary treatment included: TRT1, Low nutrient diet without emulsifier; TRT2, Low nutrient diet + 0.05% emulsifier; TRT3, High nutrient diet without emulsifier; TRT4, High nutrient diet + 0.05% emulsifier. Results showed that the nutrient density diets have no effect (P>0.05) on ATTD and AID of amino acids. However, ATTD of dry matter, nitrogen, gross energy (GE) and crude protein and essential amino acid of lysine, valine, tryptophan and total essential amino acid and non-essential amino acid of proline and alanine, AID of dry matter and GE and essential amino acid of histidine and tryptophan and non- essential amino acid of proline and alanine were significantly increase (P <0.05) in chickens fed the emulsifier compared with the nutrient density. Therefore, high nutrient density diets emulsifier supplementation had a beneficial effect on ATTD and AID of amino acids.